2018
DOI: 10.1159/000487454
|View full text |Cite
|
Sign up to set email alerts
|

Microarray Expression Profile of Circular RNAs in Peripheral Blood Mononuclear Cells from Active Tuberculosis Patients

Abstract: Background/Aims: Dysregulated expression of circular RNAs (circRNAs) was demonstrated to be implicated in many diseases. Here, we aimed to determine circRNA profile in peripheral blood mononuclear cells (PBMCs) from active tuberculosis (TB) patients to identify novel biomarkers for TB. Methods: Expression profile of circRNAs in PBMCs from 3 active pulmonary TB patients and 3 healthy controls were analyzed by microarray assay. Six circRNAs were selected for validation using real time-quantitative PCR (qRT-PCR) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 23 publications
2
53
0
3
Order By: Relevance
“…Some circRNAs displayed stress‐specific expression patterns. For instance, 37 circRNAs were differentially expressed in peripheral blood mononuclear cells in active tuberculosis patients . In human umbilical venous endothelial cells, a significant up‐regulation of circRNAs was identified to respond to hypoxia .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some circRNAs displayed stress‐specific expression patterns. For instance, 37 circRNAs were differentially expressed in peripheral blood mononuclear cells in active tuberculosis patients . In human umbilical venous endothelial cells, a significant up‐regulation of circRNAs was identified to respond to hypoxia .…”
Section: Discussionmentioning
confidence: 99%
“…For instance, 37 circRNAs were differentially expressed in peripheral blood mononuclear cells in active tuberculosis patients. 21 In human umbilical venous endothelial cells, a significant up-regulation of circRNAs was identified to respond to hypoxia. 22 Here we report, for the first time, the circRNA and mRNA transcriptome profiles of the HSAECs under stimulation of CSE.…”
Section: The Prediction Of Circrna-mediated Cerna Networkmentioning
confidence: 99%
“…Despite increasing evidence that circRNAs widely participate in human diseases exist, the role of circRNAs in TB patients is largely unknown. Our previous study revealed some circRNAs were differentially expressed in the PBMCs between TB patients and healthy controls (Huang et al, 2018 ). In this study, the differentially expressed circRNAs in the plasma of TB patients were screened in a new cohort of subjects, the roles of plasma circulating circRNAs as novel biomarkers for active TB diagnosis were also investigated.…”
Section: Introductionmentioning
confidence: 98%
“…However, the three dysregulated circRNAs were not observed in the previous findings mentioned above. 13,15,21 This F I G U R E 4 Detailed presentation of interactions between hsa_circRNA_101128 and its five potential miRNA targets. The 2D structure displayed the MRE sequence, pairing of miRNA target nucleotides and seed type.…”
Section: Discussionmentioning
confidence: 99%